Modernity, Globalization, and Human Civilization - Yogie Pranowo (Universitas Katolik Parahyangan, 2024)
The study of modernity reveals significant transformations in both space and time, accompanied by a shift from traditional to digital modes of thinking. Anthony Giddens, a prominent scholar in the discourse of modernity, emphasizes the interconnectedness of capitalism, industrialism, surveillance, and military power, highlighting their inseparability. Capitalism operates as a system of commodity production, centered on the relationship between private capital rights and labor devoid of ownership rights. Industrialism involves the efficient utilization of material resources for production purposes. Surveillance encompasses the collection, control, and supervision of information and individual activities, particularly in political domains. Meanwhile, military power characterizes a modern state's ability to monopolize the use of mobilizing forces. The main issue to be researched is how the interconnectedness of capitalism, industrialism, surveillance, and military power in the context of modernity influences the social dynamics of society. This research is significant in understanding the complex network of modern society and addressing the challenges faced, particularly regarding rapid social changes and the complexity of relationships between economic, political, and military forces.